A genealogy of the gentleman : women writers and masculinity in the eighteenth century - Harris, Mary Beth, 1986- (Newark, DE : University of Delaware Press, 2024)
"A Genealogy of the Gentleman argues that eighteenth-century women writers made key interventions in modern ideals of masculinity and authorship through their narrative constructions of the gentleman. It challenges two latent critical assumptions: first, that the gentleman's masculinity is normative, private, and therefore oppositional to concepts of performance; and second, that women writers, from their disadvantaged position within a patriarchal society, had no real means of influencing dominant structures of masculinity. By placing writers such as Mary Davys, Eliza Haywood, Charlotte Lennox, Elizabeth Inchbald, and Mary Robinson in dialogue with canonical representatives of the gentleman author - Joseph Addison and Richard Steele, David Hume, Samuel Johnson, and Samuel Richardson - Mary Beth Harris shows how these women carved out a space for their literary authority not by overtly opposing their male critics and society's patriarchal structure, but by rewriting the persona of the gentleman as a figure whose very desirability and appeal were dependent on women's influence. Ultimately, this project considers the import of these women writers' legacy, both progressive and conservative, on hegemonic standards of masculinity that persist to this day"--
Gentleman spectator as desiring author: The spectator and Mary Davys' Reform'd coquet -- The gentleman of letters as passionate reader: Eliza Haywood's Love in excess and David Hume's philosophy of moral sympathy -- Romancing the gentleman critic: reading criticism as generic courtship in Charlotte Lennox's The female Quixote and Samuel Johnson's The rambler -- "Smartly dealt with; especially by the ladies": the women writers of Samuel Richardson's Sir Charles Grandison -- The gentleman as authorial drag: inverting plots, homosociality, and moral authorship in Elizabeth Inchbald's A simple story and Mary Robinson's Walsingham -- Coda: But they were all written by women.
Includes bibliographical references and index.
Keywords: English literature -- Women authors -- History and criticism; English literature -- 18th century -- History and criticism; Masculinity in literature; Men in literature; LITERARY CRITICISM / Women Authors; LITERARY CRITICISM / Subjects & Themes / Women; Literary criticism